Solitary Solutions and Modulation Instability Analysis of the Nonlinear Schrodinger Equation with Cubic-Quartic Nonlinearity - Aslan, Ebru Cavlak (Amer Scientific Publishers, 2017)
We report optical soliton solutions of the nonlinear Schrodinger equation with cubic-quartic nonlinearity by means of the Jacobi elliptic functions. Here, two laws of nonlinearity are considered as Kerr and Power laws. We have found the restriction conditions for the existences of dark and bright solitons. We have also studied the modulation instability analysis. Furthermore, figures for the obtained solutions are plotted.
Keywords: Optical Soliton; The NLSE with Cubic-Quartic; Modulation Instability